Web-Based Laundry Service Information System Using Rapid Application Development Method - Achyani, Yuni Eka; Aulianita, Rizki; Mukhayaroh, Anna (LPPM Universitas Bina Sarana Informatika, 2024)
In the current era of digitalization, human needs for time make all household and community activities want to be practical, especially such as washing clothes. Especially for people who have busy demands and do not have time to wash clothes, dry and iron so they prefer to entrust their laundry to the services of a laundry or laundry, for the reason of saving time and to concentrate more on completing their work. This study aims to design a service information system that can help in conveying information about laundry and knowing the valid and efficient website-based laundry service information system. This form of research uses the Rapid Application Development method to produce a product and uses a prototype model to design the system. This Information System is the best solution for solving problems in the management of laundry service systems. With the use of computer data technology that is managed becomes faster, reducing time inefficiencies and reducing the occurrence of errors in processing data.